2013
DOI: 10.1016/j.jelekin.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among the muscle strength properties as assessed through various tests and variables

Abstract: We tested the hypotheses that the individual strength properties depend on the applied test and the variable extracted, rather than on the muscle group tested. Flexor and extensor muscles acting in the knee and elbow joint were tested in 58 participants. The standard strength test (SST; based on sustained maximum contraction) and alternating consecutive maximum contractions (ACMC; alternating contractions of antagonistic muscles) performed under static conditions were separately applied to provide the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(95 reference statements)
1
4
0
1
Order By: Relevance
“…Nevertheless, note that the observed moderate generalizability of the F-V parameters could be in line with recent studies revealing weak generalizability of strength measures across the individual muscles of the muscular system (Bohannon, 2008) or functional movements (Pojednic et al, 2012). Note that different variables observed by employing different methods might strongly correlate within the same muscle, but weakly across the muscular system in general (Bozic et al, 2013; Prebeg et al, 2013). …”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, note that the observed moderate generalizability of the F-V parameters could be in line with recent studies revealing weak generalizability of strength measures across the individual muscles of the muscular system (Bohannon, 2008) or functional movements (Pojednic et al, 2012). Note that different variables observed by employing different methods might strongly correlate within the same muscle, but weakly across the muscular system in general (Bozic et al, 2013; Prebeg et al, 2013). …”
Section: Discussionsupporting
confidence: 87%
“…Thus, the indices of explosive strength were introduced for the purpose of a predisposing risk factor for an ACL injury [18], and as a complementary measure to maximum strength aimed to follow up the recovery of muscle function after an ACLR [17]. Note that although a positive relationship between the maximum and explosive strength has been documented [19, 25, 26], the same muscle abilities should also be partly independent [19, 20, 27]. Namely, previous studies have suggested that short-term improvements in explosive and maximum force production may require distinct training stimuli that elicit specific adaptations (e.g., high-load contractions have proved effective in increasing maximum strength, while there is equivocal evidence for its effects on explosive force production).…”
Section: Introductionmentioning
confidence: 99%
“…Ao considerarmos que a ação isocinética exige uma produção de força tanto da musculatura agonista quanto na antagonista, era esperado a existência de relações distintas, seja por segmento corporal, grupo muscular envolvido, ou mesmo a resposta intraindividual. Neste contexto, têm sido reportado que a expressão da força em amplitudes diferentes pode induzir respostas distintas 16,17 . No presente estudo, as variáveis da função muscular foram avaliadas apenas na velocidade angular 60º/s que em certa medida podem representar angulações mais próximas das ações especificas realizadas no futebol.…”
Section: Resultsunclassified